IFIX - inductive data acquisition system: system for sub ice shelf data acquisition - Lothe, Torleif (Filchner-Ronne Ice Shelf Programme. Report, 2000)
Keywords: Antarktis; Sørishavet; forskning; teknologi

Oceanographic observations south of Berkner Island: preliminary results - Nicholls, Keith W; Østerhus, Svein; Makinson, Keith; Johnson, Mark (Filchner-Ronne Ice Shelf Programme. Report, 2000)
Keywords: Sørishavet; oseanografi

Hvite horisonter - Oterhals, Leo (Lagunen, 2000)
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie

Havforskning i tung sjø - Schwach, Vera (Havet, fisken og vitenskapen: fra fiskeriundersøkelser til havforskningsinstitutt 1860-2000, 2000)
Keywords: Sørishavet; forskning; historie; hvalfangst; pelagisk

Pingviner - Skår, Astrid (Landbruksforlaget, 2000)
Keywords: Antarktis; Sørishavet; fugler; zoologi

Emerging Law of the Sea Issues in the Antarctic Maritime Area: A Heritage for the New Century? - Vidas, Davor (Ocean Development & International Law, 2000)
This article focuses on three emerging law of the sea issues for states cooperating in management of the Antarctic and its maritime area. The first of these is no newcomer: How to regulate the dramatic increase in illegal, unregulated and unreported fishing of Patagonian toothfish (Dissostichus eleginoides) in the Southern Ocean? The second question, according to the letter of the UN Convention on the Law of the Sea, awaits the countries claiming sovereignty over portions of territory in the Antarctic 10 years from the entry into force of the Convention for each of them. The question here is what to do with the requirement contained in that Convention relating to the submission of information on the outer limit of the continental shelf beyond 200 nautical miles to the Commission on the Continental Shelf? Finally, there is a third tricky question: Who is competent to regulate, and accordingly to ban, mineral activities in the Southern Ocean seabed? Is it the International Seabed Authority as the global body, or the Antarctic Treaty Consultative Parties through their regional cooperation? This question may well never be put on the policy agenda for any global forum; but it may well be posed at any time and by any third party, whether in the UN General Assembly or, more likely, in the Assembly of the International Seabed Authority.
Keywords: Antarktis; Antarktistraktaten; Sørishavet; fiskeri; havrett; internasjonal rett; kontinentalsokkel

Postsealing genetic variation and population structure of two species of fur seal (Arctocephalus gazella and A. tropicalis) - Wynen, Louise P.; Goldsworthy, Simon D.; Guinet, Christophe; Bester, Marthán N.; Boyd, Ian L.; Gjertz, Ian; Hofmeyr, Greg J. G.; White, Robert W. G.; Slade, Rob (Molecular Ecology, 2000)
Abstract Commercial sealing in the 18th and 19th centuries had a major impact on the Antarctic and subantarctic fur seal populations (Arctocephalus gazella and A. tropicalis) in the Southern Ocean. The intensive and unrestricted nature of the industry ensured substantial reductions in population sizes and resulted in both species becoming locally extinct at some sites. However, both species are continuing to recover, through the recolonization of islands across their former range and increasing population size. This study investigated the extent and pattern of genetic variation in each species to examine the hypothesis that higher levels of historic sealing in A. gazella have resulted in a greater loss of genetic variability and population structure compared with A. tropicalis. A 316-bp section of the mitochondrial control region was sequenced and revealed nucleotide diversities of 3.2% and 4.8% for A. gazella and A. tropicalis, respectively. There was no geographical distribution of lineages observed within either species, although the respective ΦST values of 0.074 and 0.19 were significantly greater than zero. These data indicate low levels of population structure in A. gazella and relatively high levels in A. tropicalis. Additional samples screened with restriction endonucleases were incorporated, and the distribution of restriction fragment length polymorphism (RFLP) and sequence haplotypes were examined to identify the main source populations of newly recolonized islands. For A. tropicalis, the data suggest that Macquarie Island and Iles Crozet were probably recolonized by females from Marion Island, and to a lesser extent Ile Amsterdam. Although there was less population structure within A. gazella, there were two geographical regions identified: a western region containing the populations of South Georgia and Bouvet?ya, which were the probable sources for populations at Marion, the South Shetland and Heard Islands; and an eastern region containing the panmictic populations of Iles Kerguelen and Macquarie Island. The latter region may be a result of a pronounced founder effect, or represent a remnant population that survived sealing at Iles Kerguelen.
Keywords: Bouvetøya; Sørishavet; genetikk; marin biologi; pinnipedier; seler